Achieving a neutral cervical spine position in suspected spinal cord injury in children: analysing the use of a thoracic elevation device for imaging the cervical spine in paediatric patients. Issue 8 (1st April 2010) - Pandie, Zaahid; Shepherd, Mike; Lamont, Tony; Walsh, Mark; Phillips, Mark; Page, Colin
Abstract : Background: Paediatric patients with suspected cervical spine injury (CSI) are routinely immobilised on a firm surface using a hard collar, which results in excessive flexion of the cervical spine due to the relatively large size of the occiput. The objective of this study was to determine whether the use of a thoracic elevation device (TED) results in a more neutral cervical spine position and reduces the occurrence of cervical spine hyperflexion. Methods: A prospective cohort study was conducted at two Emergency Departments (sites A and B) from January 2006 to May 2007. Children ≤10 years of age with suspected CSI requiring cervical imaging were included. Those at site A received a wedge-shaped TED and those at site B did not. x-Rays from both sites were analysed for flexion, extension or neutrality of the cervical spine as defined by the Cobb angle. Results: A total of 76 patients were identified at site A and site B. There were four exclusions at each site for poor quality images. 51 patients in the site A group were found to be in neutral position (71%), compared to 29 patients in the site B group (43%) (p=0.001). One patient (1%) who had a TED was found to be hyperflexed (>10 degrees), whereas 12 (18%) patients at site B were hyperflexed (p=0.001). Conclusions: The use of a TED appears to produce a greater proportion of neutral cervical spine films in children ≤10 years of age presenting for suspected CSI.